THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY INITIATIVE IN LITHUANIAN CONSTRUCTION SECTOR: SITUATION ANALYSIS (International Journal of Innovative Technologies in Economy, 2018)
The article analyzes the concept of corporate social responsibility, its assessment methods, indicators and guidelines on standards. This work also presents the analysis of Lithuanian construction sector, examines the largest companies in this area, their possibility to develop the corporate social responsibility initiative, as well as the main difficulties in implementing the principles of social responsibility. The results show that in Lithuanian construction sector the high– income companies and companies that compete in the market over 15 years do not fully use the possibility of the development of global corporate social responsibility initiative.